2019
DOI: 10.25045/jpit.v10.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Regional Leading Potential Recommendations: Implementation of Haversine Formula in Sidoarjo on Hands Mobile Applications

Abstract: Sidoarjo on Hands (SoH) is an android-based mobile application that can ease the public of Sidoarjo to get information about the potential area in Sidoarjo. SoH has gone through two stages of systems development. The deficiencies found in the earlier version include still not presenting information on the mileage of the current user site to potential desired areas that to land on. At the same time, the user also wants information about the route. The user must take this route if they would like to go to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Haversine Formula Implementation in the SoH Application The Haversine formula calculates the distance between the user's location and the intended destination point. How to calculate it as below (Purbaningtyas et al, 2019): 1. The system will retrieve the coordinate data (lat one and lon1) of the current location of the user 2.…”
Section: Haversine Methodsmentioning
confidence: 99%
“…Haversine Formula Implementation in the SoH Application The Haversine formula calculates the distance between the user's location and the intended destination point. How to calculate it as below (Purbaningtyas et al, 2019): 1. The system will retrieve the coordinate data (lat one and lon1) of the current location of the user 2.…”
Section: Haversine Methodsmentioning
confidence: 99%
“…The haversine algorithm is an example of modeling calculation in the form of trigonometry, which is applied to a round shape. This algorithm discusses the shapes of sides and angles in spherical triangles [7]. Fisgure 1.…”
Section: Haversine Formulamentioning
confidence: 99%
“…According to [13], in order to find a straight distant line between two coordinates on the earth using longitude and latitude parameters the Haversine Formula is an essential equation, this algorithm discusses the shapes of sides and angles in spherical triangles. The reliable academic authority revealed that in 1805, a scientist created a Haversine table to determine a distance between points and the Haversine equation is utilized to calculate the space between user's area and the point of planning destination [14]. The distance calculation between 2 or more mobile users is the key point that will be used as the core issue in this proposed framework in which the distance should be in meter.…”
Section: Distance Measurementmentioning
confidence: 99%
“…Additionally, Haversine formula is represented as great circle space (removal), this equation performs calculation from main point to the goal point with trigonometric work by using scope and longitude which produces distance data between two points in meters [15]. Generally, (Mobile Station) MS location is composed of two or three dimensions and it may include information such as; the latitude and longitude of where the MS is located [14]. In order to calculate the distance between two points, the Haversine formula is the proper formula in this regard, which latitude is represented as input and longitude as the initial and last point.…”
Section: Distance Measurementmentioning
confidence: 99%